Effect of Salt Stress Levels and Spray Application of Salicylic Acid on The Quantitative Content of Phenolic Compounds and Flavonoids in Basil Leaves (Ocimum basilicum L) by HPLC - Al-Fahdawi, Hiba Jomaa; Salih, Ghada Saad (American Journal of Biology and Natural Sciences, 2026)
Using high-performance liquid chromatography (HPLC), the research experiment was conducted at the College of Agriculture Research Station at Tikrit University during the 2024–2025 growing season to examine the effects of different salt stress levels and the subsequent foliar spraying of salicylic acid (SA) on the quantitative content of phenolic compounds and flavonoids in the leaves of sweet basil (Ocimum basilicum L). Four salt stress levels (0, 4, 8, and 12 dS/m2) and three salicylic acid concentrations (0, 1, and 2 mmol) with three repetitions were used in a randomized complete block design (RCBD). The findings demonstrated that vegetative development markers, including dormant height, number of branches, and leaf weight, significantly decreased under increased salt stress, reaching up to 68.9% at the maximum salinity level. On the other hand, as a defense mechanism, the leaves’ concentration of flavonoid and phenolic chemicals rose. Rosmarinic acid, cicuric acid, chlorogenic acid, caffeic acid, quercetin, and rutin accumulation were all improved by salicylic acid at a dosage of 1 mmol, which also considerably lessened the adverse effects of salt. The greatest concentrations of total phenolic compounds, 4924.7 mg/kg dry weight, were obtained when salinity of 8 dS/m² and salicylic acid at 1 mmol interacted.